Dignified consumption and taxi app business (Uber case) - Armas Morales, Carlos Eduardo (2018)
This article, within the current framework of the so-called collaborative economy, evaluates whether the taxi app (Uber) that offers services in Peru (Lima), do so in accordance with the minimum principles of decent consumption, that is, if they provide a good taxi transport service, taking into account that in Europe these services have been classified within the public transport of taxis (Judgment of the European Court in 2017). And on the other hand, there is a debate in Latin America, including Peru to regulate these services (two bills were submitted in 2017), which calls for a theoretical review within the framework of Peruvian economic and contractual law, evaluating whether these meets the consumer: user-client, with the guarantee of adequate security to safeguard their life, health and physical psychic integrity, ie if the service is safe for the user-client, in the sense of having a decent treatment in its consumption and given the criminal acts (robberies, attempted rape and kidnappings etc.) that have occurred and occur in Lima in the provision of this service, nevertheless we believe that this study would reflect what is happening in other parts of Peru.